2013
DOI: 10.1038/ismej.2013.207
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of Chlorobium chlorochromatii CaD3 reveals clues of the symbiosis in ‘Chlorochromatium aggregatum

Abstract: A symbiotic association occurs in 'Chlorochromatium aggregatum', a phototrophic consortium integrated by two species of phylogenetically distant bacteria composed by the green-sulfur Chlorobium chlorochromatii CaD3 epibiont that surrounds a central b-proteobacterium. The nonmotile chlorobia can perform nitrogen and carbon fixation, using sulfide as electron donors for anoxygenic photosynthesis. The consortium can move due to the flagella present in the central b-protobacterium. Although Chl. chlorochromatii Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…All genes required for the β-oxidation of long-chain fatty acids were identified, in which multiple ORFs encoding acyl-CoA dehydrogenase ( 16 ) and enoyl-CoA hydratase ( 12 ) were also detected ( Fig. 3 , Table S7 ), and this is consistent with our previous findings ( 19 ).…”
Section: Resultssupporting
confidence: 91%
“…All genes required for the β-oxidation of long-chain fatty acids were identified, in which multiple ORFs encoding acyl-CoA dehydrogenase ( 16 ) and enoyl-CoA hydratase ( 12 ) were also detected ( Fig. 3 , Table S7 ), and this is consistent with our previous findings ( 19 ).…”
Section: Resultssupporting
confidence: 91%
“…Prior studies of C. tepidum indicate that glutamine synthase/glutamine aminotransferase (GS/GOGAT) is the main route of ammonium assimilation in C. tepidum (49), which would be expected to contribute to free pools of glutamate and glutamine. Alanine dehydrogenase (ADH) has been suggested as an alternative ammonium assimilation pathway in "Chlorobium chlorochromatii" (50), which is consistent with our observation of an extractable alanine pool. This is further supported by C. tepidum transcriptome sequencing data (51), which showed that genes for GS/GOGAT (CT1411, CT0401, CT0402) and ADH (CT0650, CT0706) were expressed at similar levels.…”
Section: Discussionsupporting
confidence: 91%
“…[11] c. Division of labor is accomplished in C. aggregatum with the green sulfur photosynthesizing and the β-proteobacterium providing light-sensitive motility. [91,[13][14][15] d. Bacterial symbionts have been shown to contribute multiple processes the lichen Lobaria pulmonaria. [92,18] e. Potential roles of different organisms in methanogenic communities were determined by Embree et al demonstrating division of labor within the community.…”
Section: Discussionmentioning
confidence: 99%